"The Ruthless Story and the Future Tense" in Margaret Atwood’s "Circe/Mud Poems" - Johnston, Gordon (Studies in Canadian Literature, 1980)
Margaret Atwood’s sense of time in her poetry is meant to convey a sweeping perspective: the past for her is historical, geological and mythic as well as personal. Atwood’s poetry has moved from a preoccupation with the present to a preoccupation with the future. In her "Circe/Mud Poems," she examines the problem of inherited experience, and what this may or may not mean in terms of the future. The intellect is in opposition to the intuition. The relationship between men and women is the primary means of embodying the opposition or conflict in the poem. There are three levels of significance in these poems: the private, the banal, and the allegorical.